UMP medical refrigerator alert system using sms notification - Rushdan AmrI, Abdul Rashid (2015)
Refrigerators in hospitals, clinical laboratories, pharmacies and biotechnology research laboratories are used to place medical samples which include blood, urine, serum and tissues. These samples need to be stored properly at a constant temperature normally at 4(_1) degrees Celsius to sustain their properties when used. Thus, these medical refrigerators need to be reliable and designed to meet strict requirements established by medical authorities to ensure an optimum level of performance. The paper proposes a temperature monitoring and alert system for medical refrigerators with the aid of Short Message Service (SMS). A temperature sensor will continuously check the current temperature of a medical refrigerator and send a SMS whenever the temperature is not the same as the set temperature. The SMS will inform the user/users on the condition of the refrigerator's temperature for the user to take further actions in order to save the medical samples from getting spoilt.